Hubungan antara Keterampilan Sosial dan Regulasi Emosi dengan Penerimaan Teman Sebaya - Fatwa Wahyu; Syarifudin Syarifudin; Dwi Sona; Nuril Hidayanti (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Peer acceptance plays an important role in students' social development because it affects self-confidence, participation, and psychosocial adjustment. Observation results indicate that there are still difficulties in social interaction and emotional management in grade X students, so it is important to examine these variables. This study used a quantitative approach with a correlational design on 170 students selected through random sampling techniques at SMA Negeri 13 Samarinda. Data were collected using scales of social skills, emotional regulation, and peer acceptance that have been tested for validity and reliability. Data analysis was carried out using product moment correlation and multiple linear regression using SPSS. The results showed a positive relationship between the variables studied with different levels of strength. Social skills (X1) and emotional regulation (X2) have a correlation coefficient of r = 0.563 which is included in the moderate relationship category, indicating that the better an individual's social skills, the better their emotional regulation. The relationship between social skills (X1) and peer acceptance (Y) is also in the moderate category with r = 0.510, indicating that individuals with better social skills tend to be more easily accepted by their peers. Meanwhile, emotional regulation (X2) and peer acceptance (Y) had a low positive correlation with r = 0.252. Simultaneously, social skills and emotional regulation had a significant relationship with peer acceptance (p < 0.05). However, partial regression results showed that only social skills had a significant effect on peer acceptance, while emotional regulation did not contribute significantly. This finding suggests that social skills are a more dominant factor in influencing an individual's acceptance by their peers.